Kondisi Pengusahaan Teh di Indonesia - Antik Suprihanti (Jurnal Dinamika Sosial Ekonomi, 2000)
Indonesia is one of nation that producer and supplier ted in the world market. Indonesia tea production is held by three kind of enterpreneurship. They are government plantations (PBN), private plantations (PBS) and society plantations (PR). PBN is the biggest produser (56 percent) and the highest productivity, among of them. Export of Indonesian tea still have fluctuation in few years. It's caused by Indonesian tea market still depend on them five aim export countries. They are Pakistan, USSR, USA. England and Dutch. Therefore, economic and politic instabilities condition, changes of consumen taste that happened in these countries can make export of Indonesian tea decreasing Furthermore, production of tea in Indonesia have few challenges to developing of export. Firstly, Indonesia ha to start to expansion and promotion tea to the new markets like OKI countries and East Europe. Secondly, we have to increase demand of tea by support domestic tea consumption.Key words: Tea, production, export